2018
DOI: 10.1093/schbul/sby016.387
|View full text |Cite
|
Sign up to set email alerts
|

T111. Panss Negative Symptom Dimensions Across Geographical Regions: Implications for Social, Linguistic and Cultural Consistency

Abstract: BackgroundRecognizing the discrete dimensions that underlie negative symptoms in schizophrenia and how these dimensions are conceptualized across geographical regions may result in better understanding and treatment. The expressive-experiential distinction has been shown to have vast importance in relation to functional outcomes in schizophrenia. Previous studies have shown that the PANSS may not be equivalently rated across counties and cultures, suggesting regional differences in both symptom expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 0 publications
5
38
1
Order By: Relevance
“…In exploratory and confirmatory factor analyses, Liemburg et al (2013) found an “expressive deficit” (or expressive negative) subfactor that includes flat affect (N1 of the Negative PANSS items), poor rapport (N3), lack of spontaneity and flow of conversation (N6), mannerisms and posturing (G5), motor retardation (G7), and disturbance of volition (G13), and a “social amotivation” (or experiential negative) subfactor comprising emotional withdrawal (N2), passive/apathetic social withdrawal (N4), and active social avoidance (G16). This two-subfactor structure using PANSS negative item data from different patient samples was replicated by several other studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017; Stiekema et al, 2016) confirming the same PANSS items for the social amotivation subfactor. For the expressive negative subfactor, PANSS items were the same across studies except for the PANSS disturbance of volition item (G13), which was included in only two studies (Liemburg et al, 2013; Stiekema et al, 2016), but not in the other three studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017).…”
Section: Introductionsupporting
confidence: 70%
“…In exploratory and confirmatory factor analyses, Liemburg et al (2013) found an “expressive deficit” (or expressive negative) subfactor that includes flat affect (N1 of the Negative PANSS items), poor rapport (N3), lack of spontaneity and flow of conversation (N6), mannerisms and posturing (G5), motor retardation (G7), and disturbance of volition (G13), and a “social amotivation” (or experiential negative) subfactor comprising emotional withdrawal (N2), passive/apathetic social withdrawal (N4), and active social avoidance (G16). This two-subfactor structure using PANSS negative item data from different patient samples was replicated by several other studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017; Stiekema et al, 2016) confirming the same PANSS items for the social amotivation subfactor. For the expressive negative subfactor, PANSS items were the same across studies except for the PANSS disturbance of volition item (G13), which was included in only two studies (Liemburg et al, 2013; Stiekema et al, 2016), but not in the other three studies (Fervaha et al, 2014; Jang et al, 2016; Khan et al, 2017).…”
Section: Introductionsupporting
confidence: 70%
“…To assess the multidimensional aspect of negative symptoms, changes from baseline to week 26 on the individual items of the PANSS-FSNS were evaluated. Additional PANSS-derived factors for negative symptoms [30][31][32][33] were located through an extensive search of the literature and our data were further analyzed using these models ( Table 1). Factors of interest in other domains (supplementary Table 1), including disorganized thoughts (items N5, P2, G5, G10-11, G13, G15) [24], prosocial function (items N2, N4, N7, P3, P6, G16) [34], and cognition (items N5, N7, P2, G10-11) [35], were also evaluated.…”
Section: Post Hoc Analysesmentioning
confidence: 99%
“…Further, when social competence, social cognition, and negative symptoms were used to predict social outcomes, it was also found that the same amount of variance, 32%, was shared with social outcomes. Only two of the PANSS negative symptoms predicted everyday social outcomes, passiveapathetic social withdrawal and active social avoidance, and these symptoms were found to load on a factor reflecting reduced emotional experience in a very large sample study (n=6889; Khan et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…A two-factor model of expression and experience was created and tested in several samples in a study by Khan et al (2017). The model as also examined for its link to functional outcomes (Harvey et al, 2017;Strassnig et al, 2018).…”
Section: Negative Symptom Modelsmentioning
confidence: 99%
See 1 more Smart Citation